2010
DOI: 10.3109/09637486.2010.487480
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 1-year dietary intervention with n-3 polyunsaturated fatty acid-enriched olive oil on non-alcoholic fatty liver disease patients: a preliminary study

Abstract: The results of this preliminary study showed that long-term consumption of olive oil enriched with n-3 PUFA in patients with NAFLD is able to decrease circulating liver enzymes and triglycerides, with a significant improvement of adiponectin levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
2
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(111 citation statements)
references
References 16 publications
3
101
2
4
Order By: Relevance
“…This is highly relevant because dietary 3 PUFAs are being evaluated as treatment strategies for NAFLD/NASH in children and adults (30)(31)(32)(33)(34)(35)63 ). Although these clinical studies show that dietary 3 PUFAs reduce liver fat (30)(31)(32)(33)(34)(35)(36)(37), some clinical trials have reported that 3 PUFAs, like fi sh oil ( 36 ) or EPA-ethyl esters ( 37 ), fail to improve fi brosis scores associated with NASH. Our previous report established that DHA was more effective than EPA at attenuating WD-induced hepatic fat, infl ammation, and fi brosis ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is highly relevant because dietary 3 PUFAs are being evaluated as treatment strategies for NAFLD/NASH in children and adults (30)(31)(32)(33)(34)(35)63 ). Although these clinical studies show that dietary 3 PUFAs reduce liver fat (30)(31)(32)(33)(34)(35)(36)(37), some clinical trials have reported that 3 PUFAs, like fi sh oil ( 36 ) or EPA-ethyl esters ( 37 ), fail to improve fi brosis scores associated with NASH. Our previous report established that DHA was more effective than EPA at attenuating WD-induced hepatic fat, infl ammation, and fi brosis ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Omega-3 PUFAs have well-defi ned effects on hepatic lipid metabolism and infl ammation ( 29,73 ), and more recently their effects on hepatic fi brosis have been noted ( 17,28,69 ). Although several human studies have provided evidence in support of using supplemental 3 PUFAs to treat NAFLD (30)(31)(32)(33)(34)(35)(36)(37), other studies suggest there may be limitations for their use in NASH treatment ( 36,37 ). In trials using either fi sh oil or EPA-ethyl ester supplements, investigators report that 3 PUFA supplements failed to improve fi brosis scores.…”
Section: Can 3 Pufa Be Used To Treat Human Nash?mentioning
confidence: 99%
“…In contrast, no patient achieved complete regression in the group that received only the AHA diet, and only 27.7% of them presented some reduction in the steatosis [86] . Another study employing low dose of n-3 PUFA supplementation (0.83 g/d, of which 0.47 g of EPA and 0.24 g of DHA) in olive oil demonstrated improvement in the liver echotexture (evaluated by ultrasound) and in the hepatic Doppler perfusion index, after 12 mo of treatment of NAFLD patients, compared to a control group of individuals also with NAFLD [85] . Although the investigations based on imaging methods demonstrated a reduction in liver fat as commented above, the studies that investigated the role of n-3 PUFA in NAFLD treatment using liver histology to evaluate the results have shown controversial results [88,89] .…”
Section: Nigam Et Almentioning
confidence: 99%
“…Pre-and post-intervention analysis demonstrated that the olive oil group presented increase in HDL-c levels; the canola oil group presented reduction in fasting blood glucose and TG; and both groups (olive and canola oils) presented improvement in the grade of fatty liver and liver span [82] . In several studies, the effects of the intake of n-3 PUFA supplements were investigated as a complementary treatment of NAFLD [83][84][85][86][87][88][89] . In general, these studies demonstrated a reduction in liver fat measured by different imaging methods, with the doses raging from 0.83 to 6 g/d, and duration therapy ranging from 8 wk to 18 mo [83][84][85][86][87] .…”
Section: Intrahepatocellular Lipidsmentioning
confidence: 99%
See 1 more Smart Citation